Răspuns :
0,5 - 1 / 2 x ( 3 / 4 - 0,25 ) =
= 5 / 10 - 1 / 2 x ( 3 / 4 - 25 / 100 )
= 1 / 2 - 1 / 2 x ( 3 / 4 - 1 / 4 )
= 1 / 2 - 1 / 2 x 2 / 4
= 1 / 2 - 1 / 2 x 1 / 2
= 1 / 2 - 1 / 4
= 1 / 4
= 5 / 10 - 1 / 2 x ( 3 / 4 - 25 / 100 )
= 1 / 2 - 1 / 2 x ( 3 / 4 - 1 / 4 )
= 1 / 2 - 1 / 2 x 2 / 4
= 1 / 2 - 1 / 2 x 1 / 2
= 1 / 2 - 1 / 4
= 1 / 4
[tex]0,5- \frac{1}{2} *( \frac{3}{4} - 0,25 )= \frac{1}{2} - \frac{1}{2} *( \frac{3}{4}- \frac{1}{4} )= \\ \\ \\ \\ = \frac{1}{2} - \frac{1}{2} * \frac{1}{2} = \frac{1}{2} - \frac{1}{4} =\frac{1}{4} [/tex]